Weight loss-induced improvement of body weight and insulin sensitivity is not amplified by a subsequent 12-month weight maintenance intervention but is predicted by adaption of adipose atrial natriuretic peptide system: 48-month results of a randomized controlled trial - Li, Linna; Soll, Dominik; Leupelt, Verena; Spranger, Joachim; Mai, Knut (BMC medicine, 2022)
Background Behavioral weight loss interventions are frequently hampered by long-term inefficacy. As metabolic improvements and health-related quality of life (HRQoL) are diminished by weight regain, effective long-term strategies are highly desirable. We aimed to analyze whether an additional weight maintenance intervention could delay body weight regain and can induce a long-term improvement of metabolism and HRQoL for up to 48 months in humans. Given the short-term metabolic effects of natriuretic peptides (NP), we also investigated the role of the adipose atrial NP (ANP) system in this long-term context. Methods After a successful 12-week weight reduction program 143 subjects (age>18; BMI≥27 kg/m 2 ) were randomized (1:1) to a control group or a 12-month multimodal weight maintenance intervention focusing on nutritional counseling and physical exercises. Secondary trial outcomes including course of BMI, HOMA-IR, glucose response after oGTT (glucose AUC ), and HRQoL (SF-36) were analyzed yearly for 48 months. Adipose ANP receptor mRNA expression was analyzed during weight loss. Results Initial weight loss (− 4.7±1.5 kg/m 2 ) improved glucose AUC , HOMA-IR, and HRQoL. Although BMI was still reduced after 48 months (−1.98 [95% CI −2.61, −1.35] kg/m 2 ), benefits on HOMA-IR, glucose AUC , and mental health disappeared after 36 (−0.49 [−1.00, 0.02]), 18 (0.61 [−9.57, 10.79] mg dl −1 min −1 ), and 18 months (2.06 [−0.08, 4.20]), respectively, while improved physical health persisted up to months 48 (2.95 [0.49, 5.40]). Weight maintenance intervention inhibited weight regain and delayed impairment of HOMA-IR and glucose AUC (but not HRQoL) for up to 12 months. However, no metabolic long-term effect was seen beyond the intervention period. Lower adipose NPR-C and higher NPR-A mRNA expression after weight loss predicted smaller regain of weight ( r =0.398; p <0.05)/fat mass (FM) ( r =0.391; p <0.05) and longer improvement of HOMA-IR ( r =−0.422; p <0.05), respectively. Conclusions Additional benefits of a behavioral 12-month weight maintenance intervention after weight loss regarding body weight regain and metabolic improvement does not persist beyond the intervention period. However, weight loss-induced modulation of the adipose ANP system is probably involved in the long-term control of body weight regain and insulin sensitivity. Trial registration ClinicalTrials.gov NCT00850629 . Registered on February 25, 2009.